Accounting Performance Goals in CEO Compensation Contracts and Corporate Risk Taking - Chen, Clara Xiaoling; Kim, Minjeong (MJ); Li, Laura Yue; Zhu, Wei (Management Science, 2022)
This study provides the first large-sample archival evidence on the impact of three commonly used accounting performance goals (thresholds, targets, and maximums) in CEO compensation contracts on corporate risk taking. Using proxy statement disclosure on performance goals for CEOs of U.S. public companies, we find that lower thresholds and higher maximums are associated with greater corporate risk taking, and these results are more pronounced when CEOs have greater incentives to achieve accounting performance goals or have lower innate risk aversion. In addition, we find that target difficulty is not significantly associated with corporate risk taking after controlling for thresholds and maximums. Finally, we find that CEO compensation contracts are more likely to have lower thresholds and higher maximums when risk taking is more value-enhancing or when R&D investment is more profitable, consistent with boards setting performance goals to induce an appropriate amount of corporate risk taking. Our study contributes to the accounting literature on target setting and corporate risk taking by identifying accounting performance goals as a tool in executive compensation contract design to influence risk taking. This paper was accepted by Suraj Srinivasan, accounting.